Hubungan Kemampuan Bersketsa Dengan Kemampuan Menggambar Ilustrasi Komik Di Kelas VIII MTs Al-Wardah Tembung - Aulia Syafidah; Sugito Sugito (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to prove the great contribution and significant relationship between the ability to sketch with the ability of drawing comic illustrations in the class VIII MTs Al-Wardah. The data is collected using test techniques, i.e. the test creates sketches and creates comic illustrations, the test results are then observed and evaluated by three evaluators, whose results are expressed in the form of decimals. The data was then analyzed using correlational research, data normality test using the liliefors technique, and data linearity test with the regression of the small quantum method. The results of the research showed that there was a significant relationship between the ability to sketch with the comic illustration proof of T_count 5,365 and T_ table for the degree of freedom (no) = n-k-1 = 24 on the real level (α) = 0.05 T _table = 2.064 was F_count > F_ tabel (31.44 > 4.22). The great relationship between the ability to sketch and the capacity to draw comic illustrations is collateral 0.76, and the great contribution or contribution is 59%.